Criticism of Liberals’ Call for Freedom of Thought in Ijtihad - Zainol, Nur Zainatul Nadra; Abd Majid, Latifah; Husen Ismail, Faisal; Kirin, Arwansyah (Journal of Social Transformation and Regional Development, 2021)
The main principle of liberalism is to fight for human freedom. They want free and unrestrained people. Moreover, no system of values, laws, and morals can force them to adhere to it including religions, myths, and belief systems brought in a cultural context. This thinking is contrary to the creed of Ahli Sunnah Wal Jamaah. Thus, this article explains the critique of the method of ijtihad of the liberals, namely Nasr Hamid Abu Zayd by presenting an argument to reject this method. The methodology of the study is the analysis of the contents of Nasr Hamid Abu Zayd’s book and the findings through descriptive analysis. The results of the study show that liberals support the idea of â€‹â€‹Human Rights supported by Western society. This idea is contrary to the creed of the Muslim community in Malaysia. Even ijtihad in Islam has certain conditions that must be complied with. The implications of the study show that Muslims need to be wary of accusations and allegations brought by liberals.